Adversity-Driven Growth, Not Depletion: Post-Pandemic Resilience Gains and the Persistent Gender-Perception Gap in the Indian IT Workforce - Mohite, Sonali; Agrawal, Ankur Kumar (Journal of Neonatal Surgery, 2024)
Background. The COVID-19 pandemic imposed prolonged operational and psychological strain on the global Information Technology (IT) sector(Bano et al., 2024, p. 166), raising an unresolved question: does sustained adversity deplete employee resilience or build it? Conservation-of-resources reasoning predicts erosion(Chen et al., 2015, p. 96), whereas adversarial-growth and Psychological Capital perspectives predict developable gains(Lu et al., 2022, p. 334; Luthans & Youssef‐Morgan, 2017, p. 372). Evidence from non-Western, high-precarity IT workforces is scarce(Yeo et al., 2022). Purpose. This study examines whether resilience among Indian IT professionals changed across the pandemic, whether measured resilience differs by gender, whether measured resilience aligns with workplace perceptions of who is resilient, and which organisational and individual factors predict resilience. Design/methodology/approach. A quantitative cross-sectional survey with a matched retrospective within-subjects component was administered to 405 IT professionals in Pune, India (exceeding Cochran’s minimum of 384; 75.6% in non-permanent employment). Resilience was measured using a Connor–Davidson-informed instrument. Hypotheses were tested with paired-samples and Welch t-tests, one-way ANOVA, and multiple linear regression in SPSS v28. Findings. Post-pandemic resilience exceeded pre-pandemic resilience (M = 19.37 vs 18.83; t(404) = −4.261, p < .001, d = −0.21), consistent with net adversarial growth at the population level; a dual-process interpretation in which growth and depletion co-exist cannot be excluded given the small effect and cross-sectional design. Resilience did not differ significantly by gender (t(286.29) = −0.465, p = .643), with women scoring marginally higher, yet respondents endorsed moderately strong beliefs that male colleagues are more resilient (Gender-Perception M = 18.89/25), evidencing a perception–reality gap. Employee performance (β = .370) and organisational culture (β = .323) jointly explained 34.1% of resilience variance (p < .001). Practical implications. Resilience behaved as a developable, organisationally conditioned resource that strengthened equally across gender even as stereotypes persisted, supporting a shift toward output-oriented, behaviour-anchored talent evaluation and the formal institutionalisation of flexible-work and well-being supports. Originality/value. The study provides large-sample, post-pandemic evidence on the depletion-versus-growth debate in an underexamined workforce, explicitly engaging with dual-process interpretations and the “resilience tax” risk inherent in predominantly non-permanent samples, and documents a measurable perception–reality gender gap with direct equity implications...